2020
DOI: 10.1123/japa.2019-0426
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density and Muscle Mass in Masters Olympic Weightlifters and Runners

Abstract: The authors examined the musculoskeletal implications of delayed exercise adoption in two distinct cohorts of masters athletes with ∼10 years of training experience: Olympic weightlifters (OWLs) and distance runners (RUNs). Total body and regional bone mineral density (BMD), and dual-energy X-ray absorptiometry-derived lean mass were compared in 51 OWLs and 43 RUNs. Multiple linear regression analyses were conducted on BMD and lean mass with the exercise group (i.e., OWLs vs. RUNs), age, sex, and years of expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…This exercise-induced fibre type transformation has favourable clinical implications because MHC IIx fibre percentage is negatively associated with cardiorespiratory fitness (Larsson et al 1999) and positively correlated with many key indicators of metabolic syndrome (Lillioja et al 1987;Nyholm et al 1997;Hernelahti et al 2005). Although short-term exercise training enhances skeletal muscle health, habitual exercise throughout the lifespan may confer even greater musculoskeletal advantages as has previously been observed in masters athletes (Klitgaard et al 1990b;Tarpenning et al 2004;Aagaard et al 2007;Erickson et al 2020). A recent study reported that world class masters athletes had slow muscle fibres with reduced performance compared to young adults (Power et al 2015), although no data were provided on fast muscle fibres that are repeatedly demonstrated to be more adversely affected by the ageing process.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…This exercise-induced fibre type transformation has favourable clinical implications because MHC IIx fibre percentage is negatively associated with cardiorespiratory fitness (Larsson et al 1999) and positively correlated with many key indicators of metabolic syndrome (Lillioja et al 1987;Nyholm et al 1997;Hernelahti et al 2005). Although short-term exercise training enhances skeletal muscle health, habitual exercise throughout the lifespan may confer even greater musculoskeletal advantages as has previously been observed in masters athletes (Klitgaard et al 1990b;Tarpenning et al 2004;Aagaard et al 2007;Erickson et al 2020). A recent study reported that world class masters athletes had slow muscle fibres with reduced performance compared to young adults (Power et al 2015), although no data were provided on fast muscle fibres that are repeatedly demonstrated to be more adversely affected by the ageing process.…”
Section: Introductionmentioning
confidence: 90%
“…2007; Erickson et al . 2020). A recent study reported that world class masters athletes had slow muscle fibres with reduced performance compared to young adults (Power et al .…”
Section: Introductionmentioning
confidence: 99%
“…Future research involving these cohorts should include comparisons of muscle quality and function. To elucidate whether the superior balance in the Olympic weightlifters was due to the unique, high‐velocity Olympic weightlifting stimulus or was simply a product of greater lean mass observed in this cohort, 42 future research is recommended to compare Olympic weightlifters to other competitive resistance‐trained masters athletes (eg, powerlifters).…”
Section: Discussionmentioning
confidence: 99%
“…The 'endurance phenotype' is essential for healthy cardiovascular and metabolic ageing, although strength, power and the ability to recruit a high threshold are also critical to prevent accidental falls, comprising a significant burden in the latter decades of life. For example, Master's Olympic weightlifters had significantly greater balance and lean mass than endurance runners (Erickson et al 2020), suggesting unique benefits of explosive, technically demanding exercises. Therefore, the use of strength training or plyometrics to preserve MHC IIa and neuromuscular function should be emphasized and pursued.…”
Section: Future Directionsmentioning
confidence: 99%
“…For example, Master's Olympic weightlifters had significantly greater balance and lean mass than endurance runners (Erickson et al . 2020), suggesting unique benefits of explosive, technically demanding exercises. Therefore, the use of strength training or plyometrics to preserve MHC IIa and neuromuscular function should be emphasized and pursued.…”
Section: Introductionmentioning
confidence: 99%